Postextraction Dental Implant in the Aesthetic Zone, Socket Shield Technique Versus Conventional Protocol. Issue 4 (June 2018) - Bramanti, Ennio; Norcia, Antonio; Cicciù, Marco; Matacena, Giada; Cervino, Gabriele; Troiano, Giuseppe; Zhurakivska, Khrystyna; Laino, Luigi
Abstract : Abstract: The aim of this randomized controlled trial was to evaluate the survival rate, the marginal bone level, and the aesthetic outcome; at 3 years' follow-up, of dental implants placed into a high-esthetic aesthetic zone by comparing 2 techniques of postextraction implant with immediate loading: the socket shied technique and the conventional insertion technique. Several clinical studies suggested that the avulsion of a dental element causes dimensional alterations of both soft and hard tissues at the postextractive site. To increase the aesthetic outcomes, the "socket-shield technique" has been proposed. This method involves maintaining the vestibular root portion and immediate insertion of the dental implant in close proximity to the root. Patients enrolled in this study were randomized to receive a postextraction implant in the aesthetic zone, either with the socket shied technique or with the conventional insertion technique. Implant survival, marginal bone level, and the pink aesthetic score were the outcomes evaluated. Implant survival rate was 100% in both the groups at 3 years. Implants inserted with the socket shield technique showed better values of both marginal bone level and pink aesthetic score ( P  < 0.05). Although such preliminary results need to be further confirmed, the socket shield technique seems to be a safe surgical technique that allows an implant rehabilitation characterized by better aesthetic outcomes.